PENGARUH LUAS LAHAN PANEN PADI, KONDISI JALAN, DAN JUMLAH KONSUMSI BERAS TERHADAP KETAHANAN PANGAN DI PROVINSI RIAU - Sulastri Sitohang; Wahyu Hamidi; Nobel Aqualdo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Food security is a major concern for a country / region. Food security consists of three subsystems, namely the availability, distribution, and consumption. Each subsystem has issues occurred, food production haven’t optimal due to conversion to non-agricultural land, inadequate infrastructure linking producers with consumers, and the low diversification of food consumption . The objective of this research is to know the influence of the land rice harvest, road condition, and number of rice consumption to the food availability ratio in Riau. Then to see the development of rice consumption in Riau. Data used in this research is secondary data in the form of time series of 2004-2013. Analysis method used is the method of decriptif quantitative analysis using multiple regretion analysis SPSS version of 21.0 and exponential method. The coefficient or determination (R2) 0,754 result indicates that 75,4% of food availability ratio variation can be explained by the variation of land rice harvest, road condition, and number of rice consumption. Simultaneously, all of this variables significantly influence on the food availability ratio. Partially land rice harvest and number of rice consumption significantly influence the food availability ratio and road condition is not. Then, amount of rice consumption is estimated will be increase every year.Keywords: Food Security, food availability ratio, land rice harvest, road condition, and number of rice consumption